PENGARUH PEMBERIAN TEPUNG Ulva lactuca DALAM FORMULASI PAKAN BUATAN TERHADAP INDEKS KEMATANGAN GONAD (IKG) DAN KUALITAS WARNA GONAD BULUBABI (Tripneustes gratilla) - Salmon Ratu; Agnette Tjendawangi; Lady Cindy Soewarlan (Nusa Cendana University, 2019)
This research had been done for 2 months at Balai Besar Ikan Pantai (BBIP) Tablolong. The purpose of this research is to know the effect of percentage of Ulva lactuca in feed formulation to gonad maturity index and gonad color quality of sea urchin (Tripneustes gratilla). The research method used Randomized Complete Design (RAL) with 4 treatments, namely: A (Control) 0%, B 10%, C 20% and D 30%, each treatment was repeated 3 times. The result of Variance Analysis (ANOVA) showed that C 20% treatment of Ulva lactuca gave a significant effect to gonad maturity index (GMI) with value of 6. 43% and resulted the best quality gonad color (score 4). Keyword : Tripneustes gratilla, ulva lactuca, gonad maturity index